Acetylation of Pinus radiata delays hydrolytic depolymerisation by the brown-rot fungus Rhondonia placenta. (November 2018) - Beck, G.; Hegnar, O.A.; Fossdal, C.G.; Alfredsen, G.
Abstract: Acetylation of wood can provide protection against wood deteriorating fungi, but the exact degradation mechanism remains unclear. The aim of this study was to determine the effect of acetylation of Pinus radiata wood (weight percent gain 13, 17 and 21%) on the expression of genes involved in decay by brown-rot fungus Rhodonia placenta. Gene expression analysis using qRT-PCR captured incipient to advanced decay stages. As expected the initiation of decay was delayed as a result the degree of acetylation. However, once decay was established, the rate of degradation in acetylated samples was similar to that of unmodified wood. This suggests a delay in decay rather than an absolute protection threshold at higher acetylation levels. In accordance with previous studies, the oxidative system of R. placenta was more active in wood with higher degrees of acetylation and expression of cellulose active enzymes was delayed for acetylated samples compared to untreated samples. The reason for the delay in the latter might be because of the slower diffusion rate in acetylated wood or that partially acetylated cellobiose may be less effective in triggering production of saccharification enzymes. Enzymes involved in hemicellulose and pectin degradation have previously not been focused on in studies of degradation of acetylated wood. Surprisingly, CE16 carbohydrate esterase, assumed to be involved in deacetylation of carbohydrates, was expressed significantly more in untreated samples compared to highly acetylated samples. We hypothesise that this enzyme might be regulated through a negative feedback system, where acetic acid supresses the expression. The up-regulation of two expansin genes in acetylated samples suggests that their function, to loosen the cell wall, is needed more in acetylated wood due the physical bulking of the cell wall. In this study, we demonstrate that acetylation affects the expression of specific target genes not previously reported, resulting in delayed initiation of decay. Thus, targeting these degradation mechanisms can contribute to improving wood protection systems. Highlights: Acetylation of Pinus radiata delayed Rhodonia placenta degradation. Once decay was initiated, unmodified and acetylated samples were degraded to similar degrees. Genes involved in oxidative degradation were up-regulated in wood with higher levels of acetylation. A gene encoding a carbohydrate esterase capable of deacetylating wood polymers was down-regulated in highly acetylated wood. Genes encoding expansins had higher expression levels in acetylated wood compared to unmodified wood.